Cholesterol, Statins, and Dementia: What the Cardiologist Should Know - Wanamaker, Brett L. (Clin Cardiol, 2015)
Alzheimer dementia (AD) is an important clinical problem that appears to be closely tied to comorbid cardiovascular disease, making it a relevant topic for the clinical cardiologist. Determinants of cardiovascular health, especially midlife dyslipidemia, are associated with an increased risk of dementia based on molecular and epidemiologic data. Given the potential role of dyslipidemia in the development of dementia, statins have been investigated as potential therapeutic options to slow or prevent disease. This review discusses the role of dyslipidemia and other cardiovascular risk factors in the pathogenesis of AD, with a focus on the existing evidence for the use of statin medications in the treatment and prevention of AD from observational studies and randomized clinical trials. Clinical questions for the practicing cardiologist are addressed.